Perancangan Sistem Informasi Persediaan Barang Berbasis Web Di PT. Zokkas Sejahtera Jambi - Usdeldi; Febrinita Verawati Damanik (Journal of Applied Accounting And Business, 2020)
PT. Zokkas Sejahtera Jambi is a company engaged in the storage and sale of goods (distributors). The process of data collection of incoming and outgoing goods, inventory stock, and reporting of goods was not optimal when searching for data due to the large number of data items and data containers still using spreadsheets. With that in order to be optimal, it is advisable to use an inventory information system. The purpose of this inventory information system is to solve problems that arise in the current system at PT. Zokkas Sejahtera Jambi as well as being a good solution for companies to create a faster and more accurate system for managing inventory. Methods of data collection are done by means of interviews, observation, documentation and analysis of the systems used by the company. The result of this research is to produce a web-based inventory information system with the FIFO method which provides convenience in providing information on inventory data through incoming and outgoing goods using data flow diagrams, DFD, ERD and MySQL for data processing.